DIPLOMASI SOFT POWER ASIMETRIS BERBASIS SUMBER DAYA KELAUTAN LINTAS BATAS DALAM PENYELESAIAN SENGKETA LAUT CINA SELATAN - Tahegga Primananda Alfath; Riyo Lian Nugroho (Legality : Jurnal Ilmiah Hukum, 2016)
South China Sea (SCS) conflict starting from the issuance of new maps by People’s Republic of Tiongkok in 1947, mostly claim SCS territory to bring imaginary line called the nine dash line that is based on the historical aspect. Under the UNCLOS, a claim over a territory that is based on stale Historical not justified. The nine-dash line where tensions among countries in the Neighborhood SCS, including Indonesia. There are several peaceful dispute settlement mechanism of UNCLOS including conciliation, binding settlement, arbitration, special arbitration. SCS dispute settlement should use the methods of peaceful settlement that called diplomatic win-win solution. Asymmetric soft power diplomacy that takes into account the interests of both countries and organizations will be able to be an alternative dispute resolution SCS protracted, with a record of win-win solution can be felt directly to their dispute. The method used is using the method with the approach of the Statute Law Research Approach and Conceptual Approach, supported by Legal Materials Primary and Secondary Legal Materials.